1987
DOI: 10.1007/bf00584774
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormone on the action potential and membrane currents of guinea pig ventricular myocytes

Abstract: We studied the effects of thyroid hormone on the action potential and membrane currents recorded from enzymatically dissociated guinea pig ventricular myocytes, by means of the whole-cell recording technique. Hypothyroidism was associated with an increase in action potential duration, whereas hyperthyroidism was associated with a decrease in duration. These effects are similar to those reported in multicellular preparations. Hypo- and hyperthyroidism were also associated with a decrease and an increase, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…He suggested that calcium antagonistic effects of amiodarone may play a dominant role in suppressing drug-induced early afterdepolarizations. A similar protective effect was discussed in hypothyroidism-induced QT prolongation [15,62]. Electrophysiologic changes after long-term amiodarone therapy are very similar to those during hypothyroidism, which argues for a similar cellular mode of action [208].…”
Section: Characteristics Of Proarrhythmia After Drug-lnduced Qt Prolomentioning
confidence: 74%
“…He suggested that calcium antagonistic effects of amiodarone may play a dominant role in suppressing drug-induced early afterdepolarizations. A similar protective effect was discussed in hypothyroidism-induced QT prolongation [15,62]. Electrophysiologic changes after long-term amiodarone therapy are very similar to those during hypothyroidism, which argues for a similar cellular mode of action [208].…”
Section: Characteristics Of Proarrhythmia After Drug-lnduced Qt Prolomentioning
confidence: 74%
“…Changes in electrical activity in hyperthyroid conditions have been well defined (Morkin et al 1983;Sharp et al 1985;Binah, Rubinstein & Gilat, 1987). Studies investigating underlying ionic mechanism, using voltage clamp methods, have concentrated on calcium currents.…”
Section: Introductionmentioning
confidence: 99%
“…Compelling data supporting biological activities of THs that are independent of nuclear effects came from early studies of erythrocytes (3,39,62), of myocardial membrane calciumATPase activity (212), on the rapid-onset of T3 effects on sodium and calcium currents in cardiac myocytes (18,35,222,235,236,257), and on contractile responses of vascular smooth muscle cells and resistance arteries (176,178,197). Sites of action responsible for these effects have been identified in the plasma membrane and cytosol [reviewed in (30)].…”
Section: Non-nuclear Actions Of Thsmentioning
confidence: 98%
“…In chronic thyroid disease, changes in cardiac electrophysiology have been well documented (18,131,225,280), and can be attributed to altered expression of genes including sodium-potassium ATPase (133,271) and voltage-activated K+ channels including Kv4.2, Kv4.3, and Kv1.5 (180,224,265). However, electrophysiological studies of isolated atrial and ventricular myocytes have clearly shown that pacemaker activity, repolarizing currents, and intracellular calcium can be altered rapidly by T3 independent of transcriptional changes (216,235,236).…”
Section: Th Effects On Intracellular Calcium and Ion Currentsmentioning
confidence: 99%